2003
DOI: 10.1542/peds.111.1.e39
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Supplementation With Very-Long-Chain n-3 Fatty Acids During Pregnancy and Lactation Augments Children’s IQ at 4 Years of Age

Abstract: ABSTRACT. Objectives. Docosahexaenoic acid (DHA; 22:6 n-3) and arachidonic acid (AA; 20:4 n-6) are important for development of the central nervous system in mammals. There is a growth spurt in the human brain during the last trimester of pregnancy and the first postnatal months, with a large increase in the cerebral content of AA and DHA. The fetus and the newborn infant depend on maternal supply of DHA and AA. Our hypothesis was that maternal intake of DHA during pregnancy and lactation is marginal and that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
557
3
34

Year Published

2004
2004
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 813 publications
(615 citation statements)
references
References 44 publications
21
557
3
34
Order By: Relevance
“…This tendency caused a poor fit of one of the structural equation models. Although a chance finding cannot be excluded, one must also consider the possibility that MeHg exposure may be associated with intake of essential nutrients from seafood, and that, for example, long-chain n-3 fatty acids may have beneficial effects on brain development [1,22]. Partial adjustment for this factor was provided by adding maternal fish intake during pregnancy as a covariate.…”
Section: Discussionmentioning
confidence: 99%
“…This tendency caused a poor fit of one of the structural equation models. Although a chance finding cannot be excluded, one must also consider the possibility that MeHg exposure may be associated with intake of essential nutrients from seafood, and that, for example, long-chain n-3 fatty acids may have beneficial effects on brain development [1,22]. Partial adjustment for this factor was provided by adding maternal fish intake during pregnancy as a covariate.…”
Section: Discussionmentioning
confidence: 99%
“…Certain constituents of breast milk, for example, docosahexaenoic acid, are known to be associated with infant mental development (Uauy & De Andraca, 1995;Koletzko & Rodriguez-Palmero, 1999). Docosahexaenoic acid in breast milk is associated with maternal intake of the fatty acid (Helland et al, 1998) and maternal supplementation may be favorable for later mental development of children (Helland et al, 2003). However, there is little evidence that they affect motor development.…”
Section: Discussionmentioning
confidence: 99%
“…Helland et al reported an association between the cord blood DHA at birth and one of the measures of function (cerebral maturity), although in this case the cord DHA level was also associated with gestational age, and it is not clear whether this was corrected for in the analysis. Helland et al (2003) in a subsequent study reported a positive effect on IQ at 4 years of the DHA supplementation, although the supplementation period continued throughout lactation, making it difficult to conclude whether the sensitive period was in utero or in early neonatal life when there is already some evidence for a beneficial effect of LCPUFA intake.…”
Section: Implications For Dietary Recommendationsmentioning
confidence: 99%